Regulation of fibronectin receptor distribution [published erratum appears in J Cell Biol 1992 Jul;118(2):491] (The Rockefeller University Press, 1992)
To determine the role of each intracellular domain of the fibronectin receptor in receptor distribution, chimeric receptors were constructed containing the human interleukin-2 receptor (gp55 subunit) as the extracellular and transmembrane domains, in combination with either the alpha 5 or beta 1 intracellular domain of the fibronectin receptor as the cytoplasmic domain. These chimeric receptors were transiently expressed in normal fibroblasts, and their localization on the cell surface was determined by immunofluorescence using antibodies to the human interleukin-2 receptor. The alpha 5 chimera was expressed diffusely on the plasma membrane. The beta 1 chimera, however, colocalized with the endogenous fibronectin receptor at focal contacts of cells spread on fibronectin. On cells spread in the presence of serum, the beta 1 chimera colocalized both with the fibronectin receptor at sites of extracellular fibronectin fibrils and with the vitronectin receptor at focal contacts. The beta 1 intracellular domain alone, therefore, contains sufficient information to target the chimeric receptor to regions of the cell where ligand-occupied integrin receptors are concentrated. The finding that the beta 1 chimeric protein behaves like a ligand-occupied receptor, even though the beta 1 chimera cannot itself bind extracellular ligand, suggests an intracellular difference between occupied and unoccupied receptors, and predicts that the distribution of integrin receptors can be regulated by ligand occupancy. We tested this prediction by providing a soluble cell-binding fragment of fibronectin to cells spread on laminin. Under conditions preventing further ligand adsorption to the substrate, this treatment nevertheless resulted in the relocation of diffuse fibronectin receptors to focal contacts. Similarly, a redistribution of diffuse vitronectin receptors to focal contacts occurred on cells spread on laminin after the addition of the small soluble peptide GRGDS. We conclude that the propensity for receptor redistribution to focal contacts driven by the beta 1 cytoplasmic domain alone is suppressed in heterodimeric unoccupied fibronectin receptors, and that ligand occupancy can release this constraint. This redistribution of integrin receptors after the binding of a soluble substrate molecule may provide a direct means of assembling adhesion sites.